2021
DOI: 10.1038/s41598-021-86655-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel scoring system for TIGIT expression in classic Hodgkin lymphoma

Abstract: Clinical use of immune-checkpoints inhibitors (anti PD-1/PD-L1) resulted very effective for the treatment of relapsed/refractory classic Hodgkin Lymphoma (CHL). Recently, T cell Ig and ITIM domains (TIGIT) has been recognized as an immune checkpoint receptor able to negatively regulate T cell functions. Herein, we investigated the expression of TIGIT in CHL microenvironment in order to find a potential new target for inhibitor therapy. TIGIT, PD-1 and PD-L1 expression was evaluated in 34 consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…In relapsed/refractory classic Hodgkin’s lymphoma, a TIGIT-mediated alternative system of immune escape was demonstrated to the classic PD-1/PD-L1 ( 141 ). TIGIT and PD-L1 were found to be mutually exclusively expressed and TIGIT + PD-1 + CD3 + CD4 + T cells surrounding Hodgkin Reed-Sternberg (HRS) cells were associated with advanced TNM stages ( 141 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…In relapsed/refractory classic Hodgkin’s lymphoma, a TIGIT-mediated alternative system of immune escape was demonstrated to the classic PD-1/PD-L1 ( 141 ). TIGIT and PD-L1 were found to be mutually exclusively expressed and TIGIT + PD-1 + CD3 + CD4 + T cells surrounding Hodgkin Reed-Sternberg (HRS) cells were associated with advanced TNM stages ( 141 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…This data is comparable to the other studies in which PD-1 expression was observed in less than 40% of cases (range 16–40%) [ 28 , 30 , 46 ]. TIM-3 expression was observed in 100% of adult cHL cases [ 47 ], LAG-3 expression was found in 63% of pediatric cases [ 48 ] and in 100% of adult cases [ 47 ], TIGIT expression ranged from 56% (cases where cells surrounded HRS) [ 49 ] to 100% [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and reviews reported that increased numbers of PD-1-positive cells were associated with worse outcomes and shorter survival in cHL patients [ 28 , 30 , 53 , 54 , 55 , 56 ] while other researchers showed that PD-1 expression had no significant association with survival [ 57 , 58 ]. TIGIT status did not correlate with response to treatment [ 49 ]. LAG-3 expression was not associated with survival outcomes in pediatric cases [ 48 ] but had prognostic significance in adult patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical trials targeting LAG-3 (relatlimab, NCT02061761) or TIM-3 (BMS-986258, NCT03446040) alone or in combination with nivolumab in the treatment of r/r HL are completed, and results will be released soon. In addition, T-cell Ig and ITIM domains (TIGIT) are another immune checkpoint receptor that is found to be highly co-expressed with PD-1 in r/r cHL patients [116]. Therefore, co-inhibition of PD-1 and TIGIT could be a novel strategy for treating r/r cHL.…”
Section: Other Potential Immune Checkpoint Inhibitorsmentioning
confidence: 99%